The Role of Learning Media in Improving Learning Achievement of Elementary School Students - Sri Utami, Alya; Triutami, Milda; Handayani Ningsih, Pipin (Jurnal Primagraha, 2023)
The advancement of technology has become a crucial means to achieve more effective and efficient educational goals. However, behind this, there is a significant demand for teachers to develop their skills in mastering technology and instructional media. The role of media in the teaching and learning process is highly essential for educators today. Media in learning can be used to convey messages from the sender to the receiver, and through instructional media, learners can better understand what is being communicated by the educator. Therefore, teachers are required to incorporate media in the teaching process. Utilizing instructional media can make the teaching and learning process more effective and efficient, fostering a positive relationship between teachers and students. Additionally, media can play a role in overcoming boredom in the classroom. Thus, instructional media is not only a method to address various challenges in teaching but also provides comprehensive information to learners.